A case of cerebral amyloid angiopathy associated with cerebral venous thrombosis - Komurcu, Hatice Ferhan; Okundu, Selvi; Ercan, Karabekir; Anlar, Omer (International Journal of Research in Medical Sciences, 2017)
Cerebral amyloid angiopathy is a clinical picture which is commonly seen in elderly and progressing with the deposition of amyloid in the cerebral arteries without systemic amyloidosis. We report the first case in the literature, a 71 year-old patient having an association of cerebral vein thrombosis and cerebral amyloid angiopathy presenting with recurrent cerebral hemorrhages. The cause-and-result relationship of this association of cerebral vein thrombosis and cerebral amyloid angiopathy should be investigated.